PrENGARUH.V/ARIASI.JUrMLAH.SUmDU-TERHAfDAP DiAYA OUTPUgT1PrADA2PROTObTYPE PEMBAyNGKIT2LIShTRIK> TENAxGA[MIKRO4HIuDRO0(PLrTMH) DEtNGAN9 MENGGUtNAKAN;TUoRBIN’KAPLAN - I Komang Gede Darma Yasa; I Wayan Arta Wijaya; I Made Suartika (Program Studi Teknik Elektro UNUD, 2021)
The Kaplan5Turbin is6a typepof turbine-that.can’be used=as an initial propolusion in thePLTMH system. The;Advantage; of this;Kaplan’Turbin is that it.can be;applied to;a low head with ahigh water flow rate..This study/aims;to’analyze’the’performance’of the Kaplan turbin with 5 variationsof the number of blades’consisting’of 3,4,5,6 and[7blades. The[maximum[rotational[speed[obtained bythe turbine with the;number;of;blades;5 with,an,average,value 216,8 rpm,before coupling with thegenerator. The,maximum/generator.rotational.speed that.can be.obtained.on a.turbine. that has thenumber of blades of is 865,9 rpm before .being loaded.and.749,9 rpm for the9 after load9condition .The voltage ,9current , and power9generated0are 8,7980volts, 0,419amperes,8and 3,59 wattsrespectively with a maximum torque 0,206 Nm, and efficiency of 1,53%